2022
DOI: 10.3390/cancers14051231
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts: Mechanisms of Tumor Progression and Novel Therapeutic Targets

Abstract: Cancer-associated fibroblasts (CAFs) are a heterogenous population of stromal cells found in solid malignancies that coexist with the growing tumor mass and other immune/nonimmune cellular elements. In certain neoplasms (e.g., desmoplastic tumors), CAFs are the prominent mesenchymal cell type in the tumor microenvironment, where their presence and abundance signal a poor prognosis in multiple cancers. CAFs play a major role in the progression of various malignancies by remodeling the supporting stromal matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 270 publications
(365 reference statements)
4
35
0
Order By: Relevance
“…Meanwhile, it is worth noting that cancer-associated fibroblasts were significantly upregulated in DFSP. Cancer-associated fibroblasts are a heterogeneous population of stromal cells that play a vital role in tumor progression and drug resistance ( Czekay et al, 2022 ). They also show intrastromal crosstalk with other types of immune cells, including T cells, dendritic cells, and macrophages ( Saw et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it is worth noting that cancer-associated fibroblasts were significantly upregulated in DFSP. Cancer-associated fibroblasts are a heterogeneous population of stromal cells that play a vital role in tumor progression and drug resistance ( Czekay et al, 2022 ). They also show intrastromal crosstalk with other types of immune cells, including T cells, dendritic cells, and macrophages ( Saw et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer progression has been linked to TAMs and CAFs, which have been implicated in the RAS and MAPK signaling cascades. Moreover, CAFs promote primary tumor development via the secretion of cytokines such as interleukin 1 (IL-1) [ 6 , 69 ].…”
Section: Tumor-associated Macrophages (Tams) and Cancer-associated Fi...mentioning
confidence: 99%
“…Further, cancer-associated fibroblasts (CAF) as activated by factors produced by tumor and stromal cells (e.g., TGF-β, EGF, platelet-derived growth factor and fibroblast growth factor 2) [ 32 ], support tumor growth by secreting EGF, hepatocyte growth factor, insulin growth factor-like family member (IGFL)1 and IGFL2 [ 33 ], and promote angiogenesis via VEGF release [ 34 ]. It has been shown that the crosstalk between CAF and TAM sustains tumor progression [ 35 ] and that the generation of IL-1α and IL-1β by melanoma cells may promote this malignant interaction [ 36 ].…”
Section: Tumor-induced Immune Modulationmentioning
confidence: 99%